Modelagem de parâmetros urbanísticos na cidade formal como suporte a processos de planos diretores - José Irley Ferreira Júnior (2023)
The municipality of Belo Horizonte is endowed with a high urban dynamic, making it a vibrant city in terms of its building aspect. Throughout its existence, it has developed urban regulations to facilitate city management and planning. However, it has gaps that prevent more comprehensive monitoring. The city has less than 20% of its territory with buildings that have followed the entire project approval and construction process, as evidenced by the number of lots with regular constructions compared to the whole. Challenges are imposed by the need to comply with the current Master Plan, given by Law 11.181 of 2019 in the remaining informal city, that is, in unregulated buildings. Global commitments such as the Sustainable Development Goals - SDGs and the New Urban Agenda - NUA are attributed to the Master Plan to promote a sustainable city and for the people; however, data inputs are scarce due to the focus on regulated areas of the city. In this sense, this research contributes to a new perspective by developing the Residential Lot Urban Parameters Assessment Indicator (IAPUR), based on the analysis of municipal registration data compared to the real city. The work was carried out in the so-called non-legal formal city, referring to residential lots without the building approval process and outside Villages and Shantytowns, as well as the Special Areas of Social Interest and Special Areas of Social Interest Zoning. The indicator assesses a mix of parameters that describe the morphology of the building and its behavior on the so-called CTM Lot (Municipal Technical Registry, as designated by PBH) in relation to the current Master Plan legislation. Thus, tools that support spatial information are used, considering the importance of territorial analysis for urban management and planning. Among the geoinformation technology resources used were Geographic Information Systems (GIS), Relational Database Management System (RDBMS) supporting the use of geometric (cartographic) data, and data visualization systems as output for interpreting results. Scripts were created to simulate the calculation and visualization of the main traditional urban parameters: setbacks, occupancy rates, and utilization coefficients. The systems used show good storage, manipulation, and processing capabilities, confirming that they can be used with large-scale data and quick response times. Regarding the behavior of IAPUR, the municipality showed low adherence to urban regulations and needs attention to traditional and popular neighborhoods, especially regarding setback parameters; however, it has good compliance with Utilization Coefficients, indicating that the city still has much room to grow in terms of volume. Finally, data visualization was enabled by the Dashboard tool, with the ability to offer users flexibility in handling data, according to available filters, providing new objective and clear perspectives, enabling decision-making.